STRATEGI BRANDING LAZISWAF UNIDA GONTOR DALAM OPTIMALISASI DIGITAL FUNDRAISING - veri setiawan (Jurnal Nawala Visual, 2023)
The potential for alms in Indonesia is very large, but this potential has not been fully exploited. One of the challenges is how zakat institutions create innovative strategies for collecting zakat, infaq sadaqah, and waqf in accordance with the current millennial era. In the fields of da'wah, education, social and the benefit of Muslims and received confirmation from the government. The Amil Zakat Institution in Ponorogo that develops digital fundraising is Lazizwaf Gontor. It is interesting to study how the branding strategy in optimizing digital fundraising by the amil zakat institution. The method used in this research is qualitative by using primary and secondary data sources. The data in this study were taken from four informants. Sources of data in this study came from interviews, observations, and documentation and were supported by literature in the form of books, journals, articles, and data related to this problem. Based on the results of the study, it was found that the Laziswaf Unida Gontor branding strategy in optimizing digital fundraising through the website portal and social media, Instagram. Meanwhile, digital fundraising through search engine optimized channels has not been carried out by Laziswaf Unida Gontor. This happens because the number of human resources in the field of collection and digital publication is still minimal. However, an interesting finding from this study is that the research led to findings that Laziswaf's branding strategy went through a planning process in the form of strategies for utilizing digital fundraising channels, such as website, email marketing, social media marketing, in order to collect more optimal zakat, infaq, waqf and sadaqah.. The brand development strategy carried out is to implement worship practices that show the sincerity of the brand standing above all groups. Keywords: Branding; Laziwaf; Digital Fundraising